2018
DOI: 10.1007/s00426-018-0988-5
|View full text |Cite
|
Sign up to set email alerts
|

Object discrepancy modulates feature prediction across eye movements

Abstract: Object perception across saccadic eye movements is assumed to result from integrating two information sources: incoming peripheral object information and information from a foveal prediction (Herwig and Schneider, J Exp Psychol Gen 143(5):1903-1922, 2014, Herwig, J Vis 15(16), 7, 2015). Predictions are supposed to be based on transsaccadic associations of peripheral and foveal object information. The main function of these predictions may be to conceal discrepancies in resolution and locations across saccades.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
“…Many studies demonstrated that saccadic adaptation includes a mechanism that calibrates visual space perception by observing and correcting mismatches between the peripheral view of a target and the central view of the same target after a saccade toward it (Awater et al, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins et al, 2007;Garaas & Pomplun, 2011;Gremmler et al, 2014;Zimmermann & Lappe, 2010;Zimmermann & Lappe, 2016). As mentioned earlier, similar to changing position of the target in the traditional saccadic adaptation paradigm, other features such as spatial frequency (Herwig & Schneider, 2014), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018), and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020) also appear adaptive across saccades. However, similar effects on shape and size perception have also been observed when objects were successively presented in peripheral and foveal view while observers maintained fixation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Herwig, Weiß, and Schneider (2015) demonstrated that transsaccadic associations can also be established when a geometric property, such as shape, changes transsaccadically, and swapped and normal stimuli are identified by a surface property such as colour. Köller, Poth, and Herwig (2020) showed that the effects of transsaccadic learning tend to saturate when the shape change reaches a certain magnitude, but they still occur. Learning that a square becomes a circle when fixated still makes the peripheral square look more roundish.…”
Section: Transsaccadic Re-calibrationmentioning
confidence: 99%
“…Nonetheless, it is possible that the observers get explicit feedback from the postsaccadic stimulus, and use it to change their perceptual decision criterion afterward. There is one finding that speaks against it: both observers who detect the transsaccadic change, and observers who do not detect it, show equivalent levels of re-calibration (Köller et al, 2020). One would expect that the observers who attribute their prediction error to a trick played on them by the experimenter would show a reduced re-calibration effect, if the latter depends on them noticing the transsaccadic prediction error and attributing it to a perceptual mis-judgment.…”
Section: Open Questionsmentioning
confidence: 99%